Quantum wave packet study of the He plus CaH reaction - Akpinar, Sinan; Akbalik, Firat (Elsevier Science Bv, 2010)
The He + CaH inelastic reaction is studied by a time-dependent quantum wave packet method, using the most recent potential energy surface reported by Groenenboom and Balakrishnan [1]. The state-to-state and state-to-all transition probabilities for total angular momentum J = 0 have been calculated in a broad range of collision energies. Integral cross sections and rate constants have been calculated from the wave packet transition probabilities by means of J-shifting approximation based on a capture model and a uniform J-shifting method for J > 0. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Quantum wave packet; He-CaH reaction; Inelastic scattering